The Effect of Motivation, Compensation and Work Environment on Employee Job Satisfaction at PT Pembangkit Jawa Bali (PJB) - Unit Pembangkitan (UP) Gresik - Millynda Ayu Prifaski; Maulidyah Amalina Rizqi (Universitas Muhammadiyah Gresik, 2022)
Human Resources (HR) is a central factor in an organization, which has an important role in the company as a driving factor, planning and controlling in all company activities. Therefore, it is necessary to pay attention to and create effective and efficient work, the organization needs to provide a conducive working environment, provide appropriate motivation and provide compensation which plays an important role in increasing job satisfaction so that it can influence employees to work harder and better in their work. achieve company goals. This study uses quantitative research and testing is done using multiple linear regression analysis. The number of samples in this study were 100 respondents with data collection techniques, namely by distributing questionnaires to employees via google form. In calculating the proportion of the number of samples using proportional stratified random sampling technique and sample selection using incidental sampling. The results of this study indicate that the motivation variable has a positive and insignificant effect on job satisfaction at PT Pembangkit Jawa Bali (PJB) – Unit Pembangkitan (UP) Gresik, compensation variable has a significant positive effect on job satisfaction at PT Pembangkit Jawa Bali (PJB) – Unit Pembangkitan (UP) Gresik and work environment variables have a significant positive effect on job satisfaction at PT Pembangkit Jawa Bali (PJB) – Unit Pembangkitan (UP) Gresik.